2014
DOI: 10.1002/ece3.1315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of global warming at the range margins: phenotypic plasticity and behavioral thermoregulation will buffer an endemic amphibian

Abstract: When dispersal is not an option to evade warming temperatures, compensation through behavior, plasticity, or evolutionary adaptation is essential to prevent extinction. In this work, we evaluated whether there is physiological plasticity in the thermal performance curve (TPC) of maximum jumping speed in individuals acclimated to current and projected temperatures and whether there is an opportunity for behavioral thermoregulation in the desert landscape where inhabits the northernmost population of the endemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
0
27
0
6
Order By: Relevance
“…Our results are in (partial) agreement with that expectation, as the rate at which survival changed with changes in Q 10 was very small (Table ), although the models with Q 10 still showed some support (Table ). Finally, we also expected no directional selection on T Pref as we have previously shown that acclimation to warmer temperatures produced an increase in this trait (Ruiz‐Aravena et al, ). Nevertheless, we found a nonsignificant trend showing that survival decreased, although at a very low rate, as T Pref increased, which might suggest that selection favors those individuals that are able to avoid hot microhabitats.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our results are in (partial) agreement with that expectation, as the rate at which survival changed with changes in Q 10 was very small (Table ), although the models with Q 10 still showed some support (Table ). Finally, we also expected no directional selection on T Pref as we have previously shown that acclimation to warmer temperatures produced an increase in this trait (Ruiz‐Aravena et al, ). Nevertheless, we found a nonsignificant trend showing that survival decreased, although at a very low rate, as T Pref increased, which might suggest that selection favors those individuals that are able to avoid hot microhabitats.…”
Section: Discussionmentioning
confidence: 93%
“…However, in both cases, estimates were not statistically different from zero. Nevertheless, this might suggest that selection could be favoring individuals that avoid hot microhabitats, possibly by means of behavioral responses (Ruiz‐Aravena et al, ). Indeed, behavioral thermoregulation has been proposed as one key factor that prevents an evolutionary response to selection to raising temperatures (Buckley et al, ; Huey et al., ; Kearney, Shine, & Porter, ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we evaluated the impact that dif- A major selective force in nature is exposure to environmental perturbations (Bijlsma & Loeschcke, 2005;Hoffmann & Hercus, 2000;Hoffmann & Parsons, 1991). Animals have evolved several strategies, from genetic (e.g., Alvarez, Espinoza, Inostroza B, & Arce, 2015;Hebbelmann et al, 2012;Lardies, Arias, & Bacigalupe, 2010;Silva, Bacigalupe, Luna-Rudloff, & Figueroa, 2012;Sørensen & Loeschcke, 2004), to physiological (e.g., Bozinovic, Catalán, & Kalergis, 2013;Castañeda et al, 2011;Chapin, Autumn, & Pugnaire, 2012;Hermes-Lima & Zenteno-Savìn, 2002;Uy, Leduc, Ganote, & Price, 2015) and behavioral (e.g., Kitaysky, Wingfield, & Piatt, 2001;Koolhaas et al, 1999;Ruiz-Aravena et al, 2014;Wingfield & Kitaysky, 2002) to deal with or avoid the effects of such stressors. Additionally, fitnessrelated traits are not an exception and are also affected by environmental stress (Bijlsma & Loeschcke, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence suggested that both CT min and CT max are highly flexible traits that respond to changes in temperature (Li et al ., 2009; Chanthy et al ., 2012; Ruiz-Aravena et al ., 2014; Davies et al ., 2015). As we mentioned above, there are higher inter-specific differences and variability in CT min , in comparison to CT max and T br , among X. laevis and C. gayi .…”
Section: Discussionmentioning
confidence: 99%